Ex-Migrant Nurses Empowerment after Recovery from Covid-19 Pandemic: An Analysis of Reflective Cycle Gibbs Model - Jumu, La; Hardy, Syaifoel; Riyadi, Sugeng; Arief, Dharmawan; Afzal, Ridha; Sukatemin, Sukatemin (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
During the Covid-19 outbreak, many ex-migrant nurses who had resigned and were living in Indonesia were unable to return to work. The objective of this study is to develop strategies for empowering ex-migrant nurses in the sustainable healthcare sector following the recovery from the Covid-19 pandemic. The Reflective Cycle Gibbs (RCB) model was employed during the research, which comprised six stages that began with a document review and PRISMA analysis. The PRISMA Analysis utilized Google search engines to filter documents from Google Scholar, Research Gate, and other sources. The RCB model examined 10 eligible journals and discovered records of nurses who returned to their home country due to inadequate pay, career development, workforce protection policy, and empowerment facilities. We concluded 4 problems encountered by returnee nurses i.e. lack of protection policy, poor wages, less career development, and lack of empowerment facilities.